2015
DOI: 10.1002/oby.21105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reducing portion size at a compulsory meal on later energy intake, gut hormones, and appetite in overweight adults

Abstract: Objective: Larger portion sizes (PS) are associated with greater energy intake (EI), but little evidence exists on the appetitive effects of PS reduction. This study investigated the impact of reducing breakfast PS on subsequent EI, postprandial gastrointestinal hormone responses, and appetite ratings. Methods: In a randomized crossover design (n 5 33 adults; mean BMI 29 kg/m 2 ), a compulsory breakfast was based on 25% of gender-specific estimated daily energy requirements; PS was reduced by 20% and 40%. EI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 40 publications
1
43
1
Order By: Relevance
“…The few primary studies that have assessed this directly found no such effects-for example, consumption of a reduced size of breakfast did not affect the amount of food consumed over the rest of the day. 23 Where can these interventions be made? Public sector environments Implementation of portion size interventions will be easier in public sector organisations, such as schools, hospitals, military bases, and prisons, than in commercial environments.…”
Section: Key Uncertaintiesmentioning
confidence: 99%
“…The few primary studies that have assessed this directly found no such effects-for example, consumption of a reduced size of breakfast did not affect the amount of food consumed over the rest of the day. 23 Where can these interventions be made? Public sector environments Implementation of portion size interventions will be easier in public sector organisations, such as schools, hospitals, military bases, and prisons, than in commercial environments.…”
Section: Key Uncertaintiesmentioning
confidence: 99%
“…This decision was based on factors related to both harmonisation of trade and public health, including implementation of the WHO Framework Convention on Tobacco Control (WHO FCTC), which entered into force in 2005 (World Health Organization 2003). Article 16 of the WHO FCTC prohibits the sale of cigarettes individually or in small packets on the basis that this increases their affordability to children, which aligns with evidence indicating that price is an important factor in determining smoking initiation among children and young people (Godfrey 2009; NICE 2008; Pierce 2012). As such, most of the evidence incorporated into this review relates to the effect of exposure to larger versus smaller-sized portions, packages, individual units and tableware on the selection and consumption of food (including non-alcoholic beverages, although as noted above, these were underrepresented).…”
Section: Authors' Conclusionmentioning
confidence: 69%
“…Decreased portion size at a single meal has not been shown to increase consumption at a subsequent meal ( 24 ) ; however, the effects of reduced-size entrées on intake of other menu items at the same meal are not well known, indicating that this may be an area for future study.…”
Section: Discussionmentioning
confidence: 99%